1980
DOI: 10.1172/jci109930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Role for 1,25-Dihydroxyvitamin D3 in the Pathogenesis and Treatment of X-linked Hypophosphatemic Rickets and Osteomalacia

Abstract: A B S T R A C T Although a defect in renal transportand the mineralization front activity. We, therefore, suggest that a relative deficiency of 1,25-dihydroxyvitamin D3 is a factor in the pathogenesis of X-linked hypophosphatemic rickets and osteomalacia and may modulate the phenotypic expression of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
28
0
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(32 citation statements)
references
References 44 publications
2
28
0
2
Order By: Relevance
“…The hypophosphatemia is caused by impaired proximal tubule phosphate reabsorption (1-6). The vitamin D deficiency is caused by decreased 25(OH)-vitamin D-1␣-hydroxylase activity (7)(8)(9)(10). Conventional therapy consists of oral administration of pharmacologic doses of vitamin D and phosphate, though hypercalciuria and nephrocalcinosis are frequent complications of such therapy (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…The hypophosphatemia is caused by impaired proximal tubule phosphate reabsorption (1-6). The vitamin D deficiency is caused by decreased 25(OH)-vitamin D-1␣-hydroxylase activity (7)(8)(9)(10). Conventional therapy consists of oral administration of pharmacologic doses of vitamin D and phosphate, though hypercalciuria and nephrocalcinosis are frequent complications of such therapy (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Earlier calcitriol-alone treatment in patients with XLH resulted in a smaller increase in blood phosphate than is seen in mice treated with calcitriol. (35) In spite of these issues, the data presented by Liu and colleagues (19) are convincing and may have important clinical implications. If these findings prove promising in further preclinical studies with appropriate controls, and confirmed in well-controlled studies in subjects with XLH, it could bring about a major change in the way disorders of FGF23 excess are treated.…”
mentioning
confidence: 99%
“…What is often an issue in calcitriol-alone treatment though, as was seen in these early studies, is hypercalciuria. (35,39) In conventional combined phosphate and calcitriol treatment of XLH (and other FGF23 excess disorders), nephrocalcinosis is a worrisome complication of therapy.(24) However, data from studies analyzing risk factors for nephrocalcinosis in combined phosphate and calcitriol-treated XLH patients are conflicting. Vitamin D dose (40,41) and hypercalciuria (42) appear as major factors 926 OVEJERO ET AL.…”
mentioning
confidence: 99%
See 2 more Smart Citations